Rekonseptualisasi Lembaga Keamanan Laut sebagai Upaya Mewujudkan Indonesia Menjadi Negara Poros Maritim - Salsabila, Alfian Nur; Pertiwi, Gayatri Galuh; Dewi, Popi Fitriyah (Universitas Negeri Malang, 2020)
This study aimed to find out the concept of maritime security institutions in Indonesia today and re-conceptualize the ideal sea security institutions to strengthen the existence of Indonesia as a maritime axis country. This study used the legal research method. The writing was done by reviewing library data, in the form of legislation, books, articles, journals, and others. The analysis used a SWOT analysis. The results of the study indicated that currently, institutions related to maritime security in Indonesia could not run effectively because there were too many sectoral institutions that have their respective interests, the existence of Marrine Security Agency that did not have specific authority, as well as overlapping authority between institutions. Reconceptualization of maritime security institutions needed to be done by developing and improving the status of Water Police to Maritime Police as an ideal form of maritime security.